Prioritizing Educational Media for the Golden Age: A PROMETHEE-Based Analysis of Multiple Intelligences - Rima Aprilia; Rina Filia Sari; Dedy Juliandri Panjaitan; Heba A. Fayed; Wilia Husna (Journal of Information Systems and Technology Research, 2025)
The golden age is a critical period in a child’s development, spanning from ages 0 to 8, during which learning ability, sensory functions, and emotional potential grow rapidly. At this stage, selecting appropriate educational media is crucial to optimally support the child’s multiple intelligences. In the golden age, the development of a child's memory during this period was excellent. Those at this age have the ability and enthusiasm to learn and the nature of high curiosity. This is one of the reasons for the need to optimize attention during that time. The selection of diverse educational media can determine the success factor in Conducting an analysis of the child's abilities. In this study, the research team will show how to make decisions in the selection of children's educational media by analyzing cognitive, sensory, and emotional potential using the Promethee method. This study aims to determine the most effective educational media for developing cognitive, sensory, emotional, and potential aspects of early childhood using the PROMETHEE method (Preference Ranking Organization Method for Enrichment Evaluation). PROMETHEE is a multi-criteria decision-making (MCDM) approach that helps prioritize alternatives based on predefined evaluation criteria. PROMETHEE in the last 5 years has been rarely used in the selection of educational media for early childhood in analyzing cognitive, sensory, and emotional potential. One of the methods that is often used in the selection of educational media is the ICT method. The research was conducted qualitatively in several regions of North Sumatra, involving parents of young children as key informants. The educational media analyzed included storybooks, puzzles, building blocks, and physical e-books. The response from early childhood to the sample of educational media provided is very diverse. This is based on the criteria tested on the sample. It was found that on average each sample given gave a good response to the child. Each sample given affects the testing criteria, be it cognitive, sensory, potential analysis, or children's emotions. The findings reveal that each media type influences child development differently, with physical e-books receiving the highest preference rankings. These results provide valuable insights for parents and educators in selecting educational tools that best support the optimal development of children's multiple intelligences.